2014
DOI: 10.1111/jfpp.12219
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Antioxidant Capacity of Wine Prepared from Custard Apple (Annona squamosa L.) Fruits

Abstract: The objectives of this study were to evaluate the potential of custard apple (Annona squamosa L.) in the production of a beverage fermented using Saccharomyces cerevisiae (NCIM 3282) yeast and assess the antioxidant capacity, total phenolic content and DNA damage‐protecting activity of custard apple fruit wine (CAFW). The antiradical activities of CAFW were measured using DPPH, FRAP and DMPD scavenging assays in vitro. Experimental results revealed that CAFW was not only effective in scavenging DPPH‐ and DMPD‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…Percent scavenging activities of nongerminated and germinated lentils, green gram, and black gram are shown in Figure 1. The standard curve of ascorbic acid was measured at concentrations of 1-10 mg. DPPH is a free radical that accepts a hydrogen radical to become a stable diamagnetic molecule (Jagtap and Bapat 2015). The absorption of the DPPH × radical decreases if antioxidants are present because free-radical DPPH is scavenged through hydrogen donation by antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Percent scavenging activities of nongerminated and germinated lentils, green gram, and black gram are shown in Figure 1. The standard curve of ascorbic acid was measured at concentrations of 1-10 mg. DPPH is a free radical that accepts a hydrogen radical to become a stable diamagnetic molecule (Jagtap and Bapat 2015). The absorption of the DPPH × radical decreases if antioxidants are present because free-radical DPPH is scavenged through hydrogen donation by antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is greater need to processing the ripe custard apple fruits into suitable products to minimize the post-harvest losses. Jagtap and Bapat (2014), evaluated the potential of custard apple in the production of a beverage fermented using S. cerevisiae (NCIM 3282) yeast and assessed the antioxidant capacity, total phenolic content and DNA damage-protecting activity of custard apple fruit wine. Custard apple wine showed free radicle scavenging activity towards DPPH, DMPD and FRAP.…”
Section: Custard Apple (Annona Squamosa L)mentioning
confidence: 99%
“…The radical scavenging activity of C. spinarum juice and wine may be attributed to the polyphenol and ascorbic acid content present. Moreover, in the present study DPPH scavenging activity of wine was found to be slightly higher (40.1 ± 1.8%) when compared to the fruit wines such as custrad apple (36.8 ± 0.3%) and pineapple (35.6 ± 0.4%) (Nuengchamnong & Ingkaninan, 2010;Jagtap & Bapat, 2015).…”
Section: Antioxidant Activitymentioning
confidence: 84%